2013
DOI: 10.2139/ssrn.2371024
|View full text |Cite
|
Sign up to set email alerts
|

Public Health Spending and Infant and Child Mortality in India: A State-Year Panel Analysis

Abstract: SummaryBackground: To investigate the association between public health spending and probability of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
1
1
0
1
Order By: Relevance
“…The findings indicate that expenditure on public health does not have any significant effect on under-5 mortality in Ghana. The result agrees with Kumar et al (2013) and Filmer and Lant (1999).The study further found that the availability of physician and health insurance are the major determinants of health outcomes in Ghana. Income per capita was found to be insignificant determinant of health status in Ghana and this is in line with the results of Çevik and Taşar (2013).…”
Section: Empirical Literaturesupporting
confidence: 86%
See 1 more Smart Citation
“…The findings indicate that expenditure on public health does not have any significant effect on under-5 mortality in Ghana. The result agrees with Kumar et al (2013) and Filmer and Lant (1999).The study further found that the availability of physician and health insurance are the major determinants of health outcomes in Ghana. Income per capita was found to be insignificant determinant of health status in Ghana and this is in line with the results of Çevik and Taşar (2013).…”
Section: Empirical Literaturesupporting
confidence: 86%
“…This result collaborates with the results of Anyanwu and Erhijakpor (2007), Oluwatoyin et al (2015), Okeke (2014), Arthur (2013), and so on. However, Filmer and Lant (1999), Azinim et al (2013), and Kumar et al (2013) found that there is insignificant association between public spending on health and under-5 mortality. The coefficient of government health spending is negative which implies that government health spending reduces under-5 mortality rates in Nigeria.…”
Section: Regression Results Of Under-5 Mortalitymentioning
confidence: 97%
“…A mortalidade infantil (MI) permanece como problema da atualidade e sua redução é um dos pobreza e moradias sem acesso a água potável e ao saneamento básico). Kumar et al (2013) investigaram a associação entre os gastos com saúde pública e a probabilidade de morte entre lactantes e crianças na Índia. Utilizou-se dados históricos de nascimento para criar painéis com variáveis de nascimentos no ano, óbitos infantis, gastos públicos, produção de grãos alimentares e variáveis domésticas para o período de 1980-2005. Os resultados sugerem que há uma associação entre a despesa pública de saúde e mortalidade infantil, e que alguns fatores afetam a mortalidade infantil como o sexo da criança, a ordem de nascimento, a idade da mãe, a escolaridade da mãe e a localização da residência (urbana ou rural).…”
Section: Introductionunclassified